Quantitative methods applied to asset management - Gabbi, Giampaolo (Managerial finance, 2006)
Applying strict quantitative methodology to management issues involving assets, intellectual capital or intangibles is notoriously difficult. This e-book provides an excellent exploration of these issues, and specifically analyses the optimization of asset management for pension funds, performance evaluation, fund management and strategies for portfolio optimization.